Effects of Cross-Training on Medical Teams' Teamwork and Collaboration: Use of Simulation - Ashley R. Hedges; Heather J. Johnson; Lawrence R. Kobulinsky; Jamie L. Estock; David Eibling; Amy L. Seybert (MDPI AG, 2019)
Previous research in the US Navy demonstrated that cross-training enhances teamwork and interpersonal collaboration. Limited data exists on cross-training effectiveness in medical education. This research aimed to assess whether cross-training would have similar effects on medical teams. A multidisciplinary pair of resident participants—consisting of one physician and one pharmacist—was randomly assigned to cross-training or current training condition. The training experience involved one video-based content module (training a pharmacist’s task of pharmacokinetic dosing and a physician’s task of intubation) and one simulation-based practice scenario (collaborative treatment of an unstable critically ill simulated patient). Interprofessional pairs randomized to cross-training condition participated in both the content module and practice scenario in the alternative professional role whereas pairs randomized to current training condition participated in their own professional role. Pairs also participated in pre- and post- training assessment scenarios in their own professional role. Teamwork and interprofessionalism were measured immediately following assessment scenarios. Knowledge assessments were conducted at the start and end of the scenario sequence. Multidisciplinary pairs experiencing cross-training showed a significant improvement in teamwork (increased by 6.11% vs. 3.24%, p < 0.05). All participants demonstrated significant improvement in knowledge scores (increase of 14% cross-training, p < 0.05, and increase of 13.9% control, p < 0.05). Our project suggests that cross-training can improve teamwork in interprofessional medical teams.